Model Inovasi Pengelolaan Sampah Rumah Tangga - Hayat, Hayat; Zayadi, Hasan (JU-ke: Jurnal Ketahanan Pangan, 2018)
Waste problems are endless in peoples lives. Increasing community consumptiveness towards household needs is an obstacle in handling household waste. Household waste can reach 500 ounces in one day. While the landfill (TPA) is increasingly ineffective in accommodating waste from various regions. Waste management in RW 01, Cemorokandang Urban Village, Malang City has not been handled properly and each of them does garbage disposal by transporting garbage cars with self-sufficiency in the community by paying contributions every month. A framework for organizational and management conception models is needed to provide an understanding of the community of housewives in handling the problem of waste into organic fertilizer through the separation of organic and non-organic waste. Organic waste has high economic value into organic liquid fertilizer if it is managed and handled applicatively. This, can increase public awareness in maintaining the environment and increase economic independence for the community groups RT 03 and RT 04 RW 01 Cemorokandang Village, and the people of Malang City in general. So that it can be used as a reference for the government to provide understanding and handling of waste nationally to improve the lives of social communities in safeguarding and preserving the environment and economic prosperity.